"Acquired organizational immune and its impact on the application of knowledge management strategies" Analytical study of the opinions of a sample of Lecturer staff at the Technical College of Engineering and the Technical Institute of Amara - Hassan, Fadhil Abbass (Journal of Economics and Administrative Sciences, 2021)
The present study aims to reveal the extent of the influence of the acquired organizational immune through its dimensions (organizational vaccination, organizational learning, organizational memory, and benchmarking) in the application of knowledge management strategies in its two dimensions (codification strategy, personalization strategy) as well as clarifying that influential relationship between the study variables Because of its importance in reducing resistance to change by responding to the requirements of the environment. A set of main and sub-hypotheses emerged from the study, which was formulated in view of the hypothesis scheme of the study, and in order to achieve its objectives, answer its questions and test the validity of its hypotheses, the study adopted the questionnaire as the main tool for obtaining the required data and information, as the responses of the sample members consisting of (45) individuals were analyzed. From the faculty members in both the Technical College of Engineering and the Technical Institute of Amara, and for the purpose of analyzing their responses, a number of statistical methods were used, represented by (arithmetic means, standard deviation, correlation, and multiple regression using the (SPSS) program. The results of the study confirmed the diagnosis (relationship and effect) of acquired organizational immune through its dimensions in the application of knowledge management strategies in its two dimensions (codification strategy, and personalization strategy) that it is related to a positive relationship. The management of the two organizations must study the sample and for the purpose of applying knowledge management strategies to it by strengthening it with acquired organizational immune through its approved dimensions for the purposes of the current study as an organized effort. The study reached a set of theoretical and applied conclusions, the most important of which was the existence of a positive relationship between its variables. It also proved that activating the dimensions of acquired organizational immune will lead to enhancing the application of knowledge management strategies in the two organizations studied